NOTES ON MALESIAN FERNS-I On the genus Lemmaphylluin Presl - DONK, M. A. (Research Center for Biology, 1954)
1. The genera Lepidogrammitis Ching and Weatherbya Copel.are merged in Lemmaphyllum. Presl. The inconstancy of the characters on which these genera have been separated in discussed.2. The following new combinations are proposed: Lemmaphyllum accedens (Bl.)Donk (basinym, Polypodium accedens Bl.) and Lemmaphyllum sect. Phlebodiopsis (Moore) Donk (basinym, Pleopeltis sect. Phlebodiopsis Moore).